PRINCIPLES OF IMPORT SUBSTITUTION REGARDING DRUGS - Alana Viktorovna Dzaneva; Vitalii Vladimirovich Omel'yanovskii; Saniyat Aleksandrovna Kagermazova (Фармакоэкономика)
This articles is devoted to major principles of import substitution regarding drugs within the scope of restriction lists at various levels of the health care system. The article reviews the methodology of import substitution of drugs represented as a systematic and consistent process aimed at reduction or termination of import of medical and drug products by its substitution with similar domestic products at the domestic market of the country.